Clofarabine Dosing in a Patient With Acute Myeloid Leukemia on Intermittent Hemodialysis: Case Report and Review of the Literature. Issue 6 (August 2017) - Benitez, Lydia L.; Gharibian, Katherine; Frame, David; Mody, Rajen; Mora, Erika
Abstract : Clofarabine containing chemotherapeutic regimens have demonstrated efficacy in the treatment of relapsed refractory acute myeloid leukemia. Nonetheless, there are limited data on the use of clofarabine in patients with renal failure. The present report describes the use of clofarabine in a patient with renal failure undergoing intermittent dialysis. We describe our rationale for dosing, clofarabine plasma levels obtained, and discuss our findings in the context of other available literature. Consistent with previous findings, intermittent hemodialysis was not found to be a reliable method of removing clofarabine in patients with renal insufficiency.